E-learning from the Perspective of University of Zakho Students During Covid-19. - Mohammed, Fakhir O.; Hasan, Aveen M. (Koya University Journal of Humanities & Social Sciences, 2022)
The study investigates the impressions of students at University of Zakho, Kurdistan Region of Iraq, about elearning during the Covid-19, highlighting some problems resulted from using this e-learning system. Also, the statistical significance of correlations according to gender is calculated. Using qualitative and quantitative methods for data collection, a questionnaire of seven items is utilized via google document and sent to nearly 1000 participants (males and females) via social media and online platforms. Only 752 responses returned. The data were interpreted and analyzed by Excel sheets and SPSS software. As there was statistical significance in gender differences, the results showed that the majority of the participants do not view e-learning as a fun process for their education and they have no willingness to use it for their future studies. In addition, more than half of the participants agree that (1) e-learning is costly; (2) lectures are better understood in classrooms; (3) e-learning is not adequate because of the internet and electricity outage; and (4) e-learning leads to some eye problems and headaches. Generally, knowing the students' impressions about using e-learning for their education will be helpful for the university administrators, educational policy makers, teachers to determine the students' genuine needs, motivation or challenges. This will be helpful to gain an understanding of e-learning in Kurdistan Region of Iraq, to cope with challenges involved in the process of e-learning, and develop approaches to solve the problems resulted from.